Tools and decorations made of animal bones from the archaeological site Vucedol (Vukovar, Croatia) - Babić, Krešimir (Array, 1997)
Vučedol is placed in the Panonian lowland, some 5 km from town Vukovar, on the right bank of Danube. Tools and decorations elaborated in this article originate from three eneolitic layers of Vucedol (Baden, Kostolac and Vucedol culture) and are excavate from the waste pits of Vineyard Streim (the part of multiple site Vučedol) Six group of tools and decoration were identified: sharp tools such as awls and simple knifes made of metapodium and ulnas with solid osseous substance as a main component: needles and smaller awls are made of thick tubulous bones and point if antler ; harpoons and tridents made of the point of antler ; scarpes, spatulas and chisel as dressed ribs and diaphysis of long, massive bones ; mallets for chopping grains of metapodium ; simple hoe made of Red Deer's antler ; decoration (appendage) made of roe's phalanx.